2015
DOI: 10.5152/tjg.2014.6651
|View full text |Cite
|
Sign up to set email alerts
|

The Nutritional Risk Screening 2002 tool for detecting malnutrition risk in hospitalised patients: Perspective from a developing country

Abstract: Background/Aims: To verify the validity of the Nutritional Risk Screening (NRS) 2002 test in a Turkish population. Materials and Methods: We prospectively investigated 2566 patients at a tertiary referral hospital. Nutritional status was screened using NRS 2002, and the length of the stay (LOS) was the main outcome measure. Hospital stays >10 days were accepted as prolonged LOS. NRS scores ≥3 were accepted as indicating risk for malnutrition. Statistical analyses were performed to determine the independent ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 14 publications
3
4
1
Order By: Relevance
“…Malnutrition risk is usually associated with older age, as previously reported from numerous studies ( 2 , 16 , 27 ), and additionally confirmed by our results. The mean age of our patients was 68.8 years.…”
Section: Discussionsupporting
confidence: 93%
“…Malnutrition risk is usually associated with older age, as previously reported from numerous studies ( 2 , 16 , 27 ), and additionally confirmed by our results. The mean age of our patients was 68.8 years.…”
Section: Discussionsupporting
confidence: 93%
“…Th e results of this study did not show a statistically signifi cant correlation between the length of hospital stay and the NRS score contradict the results of other studies. A substantial difference in sample size in the studies by Martins et al 26 and Gökcan et al 25 compared to the present study may account for such results.…”
Section: Discussioncontrasting
confidence: 61%
“…An extended stay was defi ned as one that lasted for more than 8 hospital days. A study with a similar objective was conducted by Gökcan et al on a sample of 2566 subjects 25 . Th e fi ndings showed that there was a statistically signifi cant correlation between the length of hospital stay and high nutritional risk.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Furthermore, as interleukin (IL)-6 measurement is not required for the 'modified' NUTRIC score [17], these tests should be feasible in many ICUs in the AsiaePacific and Middle East regions. NRS-2002 was also developed to predict the outcomes of nutritional intervention in critically ill patients, and experience in Turkey has indicated its utility in identifying malnourished patients independently of BMI [18]. However, NRS-2002 and the modified NUTRIC score are not exclusive nutritional risk assessment options [11].…”
Section: Nutritional Risk Assessment In the Icumentioning
confidence: 99%